2014
DOI: 10.1039/c4cc01118j
|View full text |Cite
|
Sign up to set email alerts
|

Octahedral-shaped perovskite nanocrystals and their visible-light photocatalytic activity

Abstract: Octahedral-shaped perovskite PbTiO3 nanocrystals (PT OCT) with well-defined {111} facets exposed have been successfully synthesized via a facile hydrothermal method by using LiNO3 as an ion surfactant. The Li-O bond on the surface of PT OCT nanocrystals is essential to the stability of such nanocrystals and also results in a dramatic high visible-light photocatalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Some interesting results have already been reported: Grewe et al [89] for example recently showed the simple hydrothermal synthesis of NaTaO 3 nanoparticles leading to the hydrogen production rate of 94 µmol/h. Yin et al [90] prepared also via hydro- thermal synthesis octahedral shaped PbTiO 3 nanocrystals with well define (111) facets that exhibit interesting performances related to the degradation of Methylene blue. These results have never been reported in conventional perovskite systems (100% degradation of Methylene blue 10 −5 M after 35 min of irradiation).…”
Section: Ternary and Quaternary Metal Oxidesmentioning
confidence: 99%
“…Some interesting results have already been reported: Grewe et al [89] for example recently showed the simple hydrothermal synthesis of NaTaO 3 nanoparticles leading to the hydrogen production rate of 94 µmol/h. Yin et al [90] prepared also via hydro- thermal synthesis octahedral shaped PbTiO 3 nanocrystals with well define (111) facets that exhibit interesting performances related to the degradation of Methylene blue. These results have never been reported in conventional perovskite systems (100% degradation of Methylene blue 10 −5 M after 35 min of irradiation).…”
Section: Ternary and Quaternary Metal Oxidesmentioning
confidence: 99%
“…According to the XPS spectra of Ti2p, O1s, and Cl2p of different TiO 2 ( Figure S2 ), it is confirmed that, as the concentration of used HCl is increased, the binding energies (458.4 eV for Ti2p 3/2 and 464.1 eV for Ti2p 1/2 ) of Ti2p, resulting from Ti 4+ , gradually increased, whereas that of O1s is almost unchanged. The XPS spectra of O1s are broad and asymmetric, implying that there exists at least two kinds of oxygen chemical states, including crystal lattice oxygen (O L ) centering at 529.5 eV and hydroxyl (O H ) one centering at 531.5 eV 16 25 . The XPS peak at 197.8 eV is mainly assigned to the chemically-adsorbed chloride (Cl − ) on the surfaces, and the amount of adsorbed chloride is increased as the rutile phase is gradually formed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, some aromatic pollutants can also cause carcinogenic and teratogenic effects [17]. Hence, various organic pollutant removal technologies has been developed, including adsorption [18,19], membrane filtration [20], photocatalytic degradation [21,22], chemical oxidation [23], flocculation [24] and electrooxidation [25]. Catalytic technology has been widely studied because of its high efficiency, simple operation, low cost, and wide range of applications [26,27].…”
Section: Introductionmentioning
confidence: 99%